Resistance of ryegrass (Lolium spp.) to paraquat and glyphosate in the Western Cape - Eksteen, Frederik Heinrich (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD) -- University of Stellenbosch, 2007.